The craft of research - Booth, Wayne C.; Colomb, Gregory G.; FitzGerald, William T.; Williams, Joseph M.; Bizup, Joseph 1966- (Chicago The University of Chicago Press, 2024)
"With more than a million copies sold since its first publication, The Craft of Research has guided generations of readers at all levels to become better researchers, thinkers, and communicators. The original authors--all of them legendary teachers--believed that research is a communal activity and illustrated how to choose meaningful topics, make sound and compelling arguments, and convey these arguments effectively in writing for the benefit of other researchers. While preserving the book's proven approach to the research process, as well as its distinctive voice and general structure, this new edition recognizes the more diverse ways research is conducted and communicated today. Thoroughly revised by Joseph Bizup and William T. FitzGerald, it acknowledges that research may end in a product other than a paper--or no product at all--and includes a new chapter about effective presentations. It features new examples on contemporary research topics and accounts for new technologies used in research, including basic guidelines for appropriate use of generative AI. And it ends with an expanded chapter on ethics that addresses researchers' broader obligations to their research communities and audiences as well as systemic questions about ethical research practices. This beloved classic is now ready for a new and more diverse generation of researchers"-- Provided by publisher.
Preface : the aims of this edition -- Introduction : your research and your audience -- Asking questions, seeking answers. From topics to questions; From questions to a problem -- Sources and resources. Finding and evaluating sources; Engaging sources -- Making your argument. Making good arguments : an overview; Making claims; Assembling reasons and evidence; Warrants; Acknowledgements and responses -- Delivering your argument. Planning and drafting; Revising and organizing; Incorporating sources; Communicating evidence visually; Introductions and conclusions; Revising style : telling your story clearly; Research presentations -- Some last considerations. The ethics of research; Advice for teachers -- Our debts -- Appendix : a brief guide to bibliographic and other resources.
Includes bibliographical references and index.
Keywords: Technical writing; Research -- Methodology